Model Order Reduction of Discrete-Time Interval Systems by Differentiation Calculus - Choudhary A.K.; Nagar S.K. (My University, 2025)
Abstract: The paper presents an algorithm for order reduction of a discrete-time interval system based on the conventional differential calculus approach. The procedure initiated for the continuous-time non-interval system advances to the discrete-time interval system in a novel manner in this paper. The proposed algorithm is computationally straightforward, simple and leads to an acceptable results as compared to the existing techniques. The examples play a significant role in establishment of the algorithm. Additionally, the limitation derived during the discourse of methodology is also accounted along with a possible future scope. © 2018, Allerton Press, Inc.